In Vitro Expression Of The Ctxb Toxin Gene Towards The Development Of A Dna Vaccine Against Cholera - Abdullah, Sharilnizam (2001)
The complete eradication of cholera is an unachievable goal because it is now firmly established that there are environmental reservoirs for Vibrio cholerae. Although there are effective treatments for this disease, they are expensive and impractical in time of epidemic. All these points lead to the fact that the development of a safe, cheap and efficient vaccine is probably the best solution to the problem. A variety of strategies have been employed to create better vaccines against cholera but these traditional vaccines produced still suffer from a number of inherent drawbacks. Therefore, a new type of cholera vaccine is being proposed which may retain all the positive aspects of the existing vaccines while avoiding their shortcomings. It belongs to a new generation of vaccines termed DNA vaccines. The development of this vaccine has been revolutionized by the finding that antigen-encoding DNA plasmids can be used to induce cellular and humoral immune responses against immunogenic determinant. In this study, the focus is on the ctxB gene, the gene encoding the B subunit cholera toxin as a potential candidate for a vaccine against cholera. The ctxB gene is required for the binding of the Cholera Toxin (CT) to the eukaryotic cell and facilitates the entry of the active toxin (CTXA) into the host cell which in turn, produces the profuse diarrheal symptom.